Associação dos fatores de risco para doenças cardiovasculares e qualidade de vida entre servidores da saúde - Barel, Matheus [UNESP] (2010)
Several public health problems are due to environmental work, which, associated with sedentarism, contribute to reduce the quality of life of the worker. Therefore, this study aimed to describe the profile, evaluate the physical condition and cardiovascular risk factor of health workers. Health workers (198) from Bauru and Jau cities (46 ± 10 years old) were assessed. They answered a questionnaire and participated in antrophometric and functional assessments. Values are presented as means ± SD. Qui-squared (x²) analysis, odds rate and Pearson correlation were used (p < 0.05). From all workers evaluated, 54% presented high body weight, 33% high blood pressure and 56% were sedentary. Total cholesterol (TC), low-density lipoprotein and triglycerides (TG) above normal values were found in 49%, 41% and 24% of the individuals, respectively, and 75% presented low values of high-density lipoprotein. Qui-squared analysis and odds rate confirmed that TG and blood pressure (BP) were higher for men compared with women. Physical capacity was bad for 56% of men and 23% of women. Also, flexibility was unsatisfactory for men and women. Body mass index correlated positively with BP, TC and TG. Aging was an important risk factor for BP, TC, blood glucose, body mass index and flexibility only for women (p < 0.05). The prevalence of multiple risk factors among these health workers shows that this population is not adequately assisted. For this reason, a program from the government in order to make this population recognize such problems and avoid premature retirement is suggested